Young people learning from digital media outside of school: the informal meets the formal - Pereira, Sara; Fillol, Joana; Moura, Pedro Filipe Ribeiro de (Comunicar, 2019)
The dissonance between what teenagers learn in classrooms and their everyday lives is not a recent phenomenon, but it is increasingly relevant as school systems are unable to follow the evolution of media and society beyond traditional concerns regarding the protection of young people. An overly scholarly view of learning continues to prevail in our society, which seems to marginalize the knowledge that young people develop with and through media and digital platforms. Based on questionnaires, workshops, and interviews conducted with Portuguese teenagers, aged 12 to 16 years old (N=78), attending an urban and a rural school in the North of the country, this paper aims to understand how these teens are learning to use the media, what motivates them, and if their media practices contribute to the acquisition of skills and competencies useful to their lives inside and outside school. The research main results confirm the existence of a gap between formal and informal education. Informal education is mainly motivated by their needs and peer influence. Colleagues and family, alongside the Internet and self-discovery, appear as important sources of knowledge. Another important conclusion is that informal learning strategies contribute to the development of skills and competencies that are useful from a school viewpoint. La disonancia entre lo que aprenden los jóvenes en clase y en su vida cotidiana no es un fenómeno reciente, pero es cada vez más relevante, ya que la escuela no es capaz, evidentemente, de acompañar la evolución. En nuestra sociedad, sigue prevaleciendo una visión demasiado escolarizada del aprendizaje, que parece marginalizar los conocimientos que los jóvenes desarrollan con y a través de los medios y de las plataformas digitales. Basado en cuestionarios, entrevistas y talleres realizados con jóvenes portugueses entre los 12 y los 16 años (N=78), de una escuela urbana y otra rural del norte del país, este artículo pretende comprender cómo están estos jóvenes aprendiendo a usar los medios, lo que les motiva y si lo que hacen con ellos contribuye a la adquisición de capacidades y competencias útiles para sus vidas dentro y fuera de la escuela. Los principales resultados de la investigación confirman la existencia de un foso entre la educación formal e informal. La educación informal es sobretodo motivada por sus necesidades y por la influencia de sus pares. Los compañeros y la familia, junto con Internet y con lo que descubren por ellos mismos, aparecen como importantes fuentes de conocimiento. También se concluyó que las estrategias informales de aprendizaje contribuyen al desarrollo de capacidades y competencias útiles desde un punto de vista escolar.